Hybridization Between Yuccas From Baja California: Genomic and Environmental Patterns - Arteaga, Maria Clara; Bello-Bedoy, Rafael; Gasca-Pineda, Jaime (Frontiers in Plant Science, 2020)
Hybridization can occur when two geographically isolated species are reproductively compatible and have come into sympatry due to range shifts. Yucca and yucca moths exhibit obligate pollination mutualism; yucca moths are responsible for the gene flow mediated by pollen among yucca populations. In the Baja California Peninsula, there are two yucca sister species, Y. capensis and Y. valida, that have coevolved with the same pollinator, Tegeticula baja. Both yucca species are endemic to the peninsula, and their current distributions are allopatric. Based on their morphological characteristics, it has been suggested that some plants growing in the southern part of the Magdalena flatland, a region outside of the current geographical range of Y. valida and Y. capensis, have hybrid origins. We conducted genomic and climatic analyses of the two yucca species as well as the putative hybrid populations. We genotyped 3,423 single nucleotide polymorphisms in 120 individuals sampled from 35 localities. We applied Bayesian tests and geographic cline analyses to the genomic data. Using climatic information from the occurrence sites, we projected species distribution models in different periods to assess changes in the distributional range, and we performed a statistical test to define the niche divergence between the paternal species and the putative hybrid populations. Structure analysis revealed mixed ancestry in the genome of hybrid populations, and the Bayesian models supported a scenario of post-divergence gene flow between the yucca species. Our species distribution models reveal that the geographical ranges of the parental species overlapped mainly during the Last Glacial Maximum, which could facilitate genetic admixture between those species. Finally, we found that most of the assessed environmental axes between the parents and hybrid populations are divergent, indicating that the climatic niche of the hybrid populations is shifting from that of the populations’ progenitors. Our results show that the populations in the southern part of the Magdalena flatland are the result of combination of the genetic components of two species. Hybrid individuals with this novel genomic combination arose in a different habitat than their parental species, and they exhibit ecological divergence, which contributes to reproductive isolation through spatial and temporal barriers.